An approach to the academic research context and Colombian political university autonomy - Leonor MOJICA SÁNCHEZ (Ediciones Universidad de Salamanca, 2017)
This article discusses the context of autonomy in three main regions: European Higher Education Area, United States and Latin America. Exposes the vision of renowned scholars on educational policies and university autonomy. Raising a chronological journey from political recognition, highlighting policies that have influenced the autonomy of universities worldwide.